Polybenzoxazole Nanofiber-Reinforced Moisture-Responsive Soft Actuators - Meiling Chen (Nature Portfolio, 2017)
Abstract Hydromorphic biological systems, such as morning glory flowers, pinecones, and awns, have inspired researchers to design moisture-sensitive soft actuators capable of directly converting the change of moisture into motion or mechanical work. Here, we report a moisture-sensitive poly(p-phenylene benzobisoxazole) nanofiber (PBONF)-reinforced carbon nanotube/poly(vinyl alcohol) (CNT/PVA) bilayer soft actuator with fine performance on conductivity and mechanical properties. The embedded PBONFs not only assist CNTs to form a continuous, conductive film, but also enhance the mechanical performance of the actuators. The PBONF-reinforced CNT/PVA bilayer actuators can unsymmetrically adsorb and desorb water, resulting in a reversible deformation. More importantly, the actuators show a pronounced increase of conductivity due to the deformation induced by the moisture change, which allows the integration of a moisture-sensitive actuator and a humidity sensor. Upon changing the environmental humidity, the actuators can respond by the deformation for shielding and report the humidity change in a visual manner, which has been demonstrated by a tweezer and a curtain. Such nanofiber-reinforced bilayer actuators with the sensing capability should hold considerable promise for the applications such as soft robots, sensors, intelligent switches, integrated devices, and material storage.